Pé diabético : percepções e orientações à um grupo de pacientes - Dalmolin, Felipe (2017)
The Diabetic Foot is considered the main complication of diabetes mellitus, characterized by foot injuries caused by trauma and deformities, associated with peripheral neuropathy; lesions that may progress to ulceration and, consequently, to amputations. Studies show that up to 50% of cases of amputation could be avoided by preventing risk factors, with educational and health promotion activities. In light of the exposed, the objective of this study was to evaluate the perception and knowledge of a group of patients with diabetes mellitus in relation to diabetic foot. The research was framed in a qualitative approach performed with members of the Happy Age group, from São Cristóvão Basic Care Unit (BCU) in Sinop, State of Mato Grosso. For that, we selected all patients that were participating in the group meetings in March and April, 2017, which were 11 diabetic patients. Data collection was performed at the patient’s home, after authorization and consent of the participant, through an interview recorded in audio and guided by a semi-structured questionnaire containing five open questions. The interviews were recorded which were later transcribed and analyzed through content analysis. This research was approved by the Ethics and Research Committee of the Federal University of Mato Grosso -Sinop Campus, no. 2,063,269. In our results, it was noticed that most of the interviewees had no knowledge about the topic of diabetic foot, neither were aware of its complications, and still less applied preventive measures for the occurrence of such complication. It was also noticeable that there is a need for a greater approach to the diabetic foot subject at the time of diagnosis and consultation. Therefore, it is important to make patients aware about what the diabetic foot is, explaining its risks and consequences, and also educate the patients to be able to take care of themselves in order to prevent such complication.